Enhancing food systems for sustainable and healthy diets through nutrition-sensitive value chains: Key insights from Malaita, Solomon Islands - Hernandez, Ricardo; Even, Brice; Nabuuma, Deborah (International Center for Tropical Agriculture (CIAT), 2025)
This brief presents key insights from the Melanesia Rural Market and Innovation-Driven (MERMAID) Programme in Malaita, Solomon Islands, where nutrition-sensitive value chains (NSVCs) were used to enhance food systems for sustainable and healthy diets. The study applied a structured four-step NSVC methodology to assess local nutrition challenges, prioritize nutrient-rich commodities, and analyze selected agri-food value chains. The process identified nutrient-rich products and practical entry points for targeted interventions that can support both dietary outcomes and livelihood opportunities. The brief outlines context-specific strategies across production, marketing, and consumption, emphasizing the importance of social inclusion, gender equity, and behavior change. It provides actionable pathways to strengthen food systems in climate-vulnerable and resource-constrained settings.